A Bibliometric Analysis of Green Finance and Waste Management in Small and Medium Enterprises (SMEs): Insights from Indonesia - Babangida, Fahad; Nurrachmi, Rininta (Research Center and Case Clearing House PPM School of Management, 2026)
This study aims to inform academics and policymakers by examining research trends on green finance and waste management in small and medium enterprises in Indonesia from 2000 to 2025, highlighting significant contributions and areas of focus. Using the PRISMA framework, a VOS viewer was used to illustrate the results of a bibliometric analysis of 10,208 articles from the Scopus database. The analysis identifies Indonesia as the top contributor, Matsumoto, T. as the most prolific author, and Universitas Indonesia as the top institution. The AIP Conference Proceedings and the IOP Conference Series Earth and Environmental Science were recognised as essential publication channels. While low-frequency phrases indicate potential avenues for future research, emerging study clusters highlight important subjects like waste management and SMEs. The analysis is restricted to English-language articles and Scopus data, excluding other databases and document formats. Future studies could use more resources and databases, such as Web of Science, Gephi, and Springer, to further understanding. This review offers innovative qualitative methodologies and comprehensive insights by mapping academic works on waste management and green finance in SMEs. Moreover, it lays the groundwork for future research on the circular economy and sustainable development. It is a valuable resource for researchers and practitioners seeking to address the challenges of green finance and waste management of SMEs in Indonesia and ultimately promote sustainable practices in the construction industry.